PENDEKATAN MAQÂSHID AL- SYARI’AH DALAM PEMIKIRAN ALI JUM’AH - Sugianto, David; Salma, Salma (UIN Imam Bonjol Padang, 2020)
The problem of this research is how to approach and apply maqâshid al-syari'ah in thinking of Ali Jum'ah. Starting from the approach of maqâshid al-shariah in maintaining the benefit of religion (hifz al-din), maintaining the benefit of the soul (hifz an-nafs), maintaining the welfare of the mind (hifz al-'aql), maintaining the benefit of the descend / nasab (hifz an-nasl) and preserves the wealth of property (hifz al-mâl).The purpose achieved in this research is to know the application of maqâshid al-syari'ah by Ali Jum'ah in thought and view and his opinion in establishing Islamic law. The extent to which maqâshid al-shari'ah is applied in terms of maintaining the good of the religion (hifz al-din), preserving the soul's goodness (hifz an-nafs), maintaining the welfare of the mind (hifz al-'aql), maintaining the good of the descendants (hifz- nasl) and maintain the wealth of property (hifz al-mal).This research is a study character of library research (library research). The main source of this research is the book al-Kalim al- Thayyib Fatawa 'Ashriyah and Fatawa Bait al-Muslim, is a book written by Ali Jum'ah. Other supporting sources include other Ali Jum'ah books such as Aliyat al-Ijtihâd, Madkhal ila Dirasah al-Mazâhib al-Fiqhiyah, Madkhal fi al-Thurâst, al-Qiyâs' Inda Ushuliyyin, and other books by others support and refine this research.The results of this study can be concluded that some thoughts and fatwa of Ali Jum'ah when associated with maqâshid al-syari'ah (the purpose of legal pensyariatan) in the five elements that exist; keeping religion, soul, mind, descendant, and treasure, apparently has a common point in its application.One of the thoughts of Ali Jum'ah with the approach of maqâshid al-syari'ah in the element of maintaining the benefit of religion (hifz al-din) is about pilot fasting in Ramadan. Ali Jum'ah says if conditions allow for fasting, then may choose between fasting and not fasting. But if conditions are very difficult to fast that can bring harm, then obliged to break (not fasting) and forbidden fasting. In maintaining the benefit of the soul (hifz an-nafs) there are cases concerning the law of organ transplantation. According to Ali Jum'ah, both transplants from humans who live to other living human beings, as well as corpse organs to living humans are allowed by shari'ah if they meet certain conditions. In maintaining the benefit of reason (hifz al-'aql) the author finds the approach of maqâshid al- syari'ah on his fatwa and his thoughts when asked the law of narcotics. Ali Jum'ah only describes the laws and postulates of the Qur'an and Sunnah regarding the law of khamar, without harmonizing the connection of narcotics and khamar. In maintaining the benefit of offspring (hifz an-nasl) the author finds the maqashid al-shari'ah approach on the fatwa on the law of sterilization in humans. According to Ali Jum'ah, such sterilization is haram, if not in an emergency or dangerous. A person is not required to do so if it does not harm him or does not inflict damage on him. As for maintaining the wealth of property (hifz al-mâl) one example of maqâshid al-syari'ah approach to the sale and purchase of land but not face to face between the seller and the buyer. In this case, Ali Jum'ah advised against buying and selling in this condition, for fear of greater harm and wasted loss and futility.Keyword; Ali Jum'ah, Maqâshid Al-Syari’ah, Approach